Review of the Granting of Cultivation Rights on Land Management Rights Based on Positive Law - Setiawan, Muhammad Rifaldi; Anugerahayu, Ayang Afira (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This study is a normative investigation that seeks to evaluate the review process associated with the allocation of HGU on HPL land. This regulation stands in contradiction to the UUPA, which stipulates that HGU should only be assigned on state-owned land; however, the legitimacy of the recent regulations offers a pathway for granting HGU on HPL territory. Additionally, this paper employs both the statutory approach and the conceptual approach. Legally speaking, the UUPA does not recognize HPL as a "land right," but rather designates it as "management." HPL emerged as one of the land rights through the Agrarian Ministerial Regulation No. 9 of 1965 and has evolved to the present as outlined in PP 18 of 2021. Perspectives regarding the definition of "management" differ. The UUPA defines "management" as authority, whereas PP 18 of 2021 interprets "management" as a form of land right. Moreover, concerning the HGU concept addressed in Article 28 of the UUPA, the land allocation must originate from the state's direct control, rather than from land that has been utilized by the holder of the HPL certificate for agricultural, fishery, or livestock purposes. This discrepancy clearly indicates conflicting norms, resulting in legal ambiguity and a possibility for judicial review.